Improved properties of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) produced by Comamonas sp. EB172 utilizing volatile fatty acids by regulating the nitrogen source - Zakaria @ Mamat, Mohd Rafein; Ariffin, Hidayah; Abd. Aziz, Suraini; Hassan, Mohd Ali; Shirai, Yoshihito (Hindawi Publishing Corporation, 2013)
This study presents the effect of carbon to nitrogen ratio (C/N) (mol/mol) on the cell growth and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) accumulation by Comamonas sp. EB172 in 2 L fermenters using volatile fatty acids (VFA) as the carbon source. This VFA was supplemented with ammonium sulphate and yeast extract in the feeding solution to achieve C/N (mol/mol) 5, 15, 25, and 34.4, respectively. By extrapolating the C/N and the source of nitrogen, the properties of the polymers can be regulated. The number average molecular weight (M n) of P(3HB-co-3HV) copolymer reached the highest at 838 × 10 3 Da with polydispersity index (PDI) value of 1.8, when the culture broth was supplemented with yeast extract (C/N 34.4). Tensile strength and Young's modulus of the copolymer containing 6-8 mol% 3HV were in the ranges of 13-14.4 MPa and 0.26-0.34 GPa, respectively, comparable to those of polyethylene (PE). Thus, Comamonas sp. EB172 has shown promising bacterial isolates producing polyhydroxyalkanoates from renewable carbon materials.